Protein-enhanced small molecule disruptors of ordered membrane domains - Katherine M. Stefanski; Geoffrey C. Li; Dustin D. Luu; Kelvin K. Fosu; Eduardo Guadarrama; James M. Hutchison; Nilabh Saksena; Yelyzaveta Zuy; Alexander J. Fisch; Thomas P. Hasaka; Joshua A. Bauer; Alfred L. George; et al. (Proceedings of the National Academy of Sciences, 2026)
Membrane order and fluidity influence many biological processes. However, tools to manipulate membranes under physiological conditions have been limited. In the process of high-throughput screening for molecules that shift the phase partitioning between ordered and disordered membrane phases of the tetraspan membrane protein peripheral myelin protein 22 (PMP22), we identified two chemically similar compounds, VU0615562 and VU0619195, that shift PMP22 toward the disordered phase and destabilize the “lipid raft”-like ordered phase. Follow-up experiments showed that this latter activity is, counterintuitively, enhanced by the presence of PMP22, which normally stabilizes the ordered phase. Biophysical studies indicate that these compounds reduce raft stability through a mechanism that involves both direct interactions with proteins and the disruption of lipid packing. We further observed that acute treatment of live cells with VU0619195 modulated membrane fluidity and TRPM8 channel function while both compounds altered KCNQ1 channel activity, providing examples of practical applications for these compounds. These protein-enhanced raft modulators reveal distinct lipid and protein-based forces that destabilize membrane order and may be useful as pharmacological tools for manipulating and probing the biological roles of ordered membrane domains in cells.